2020
DOI: 10.1089/jmf.2019.0183
|View full text |Cite
|
Sign up to set email alerts
|

Nattospes as Effective and Safe Functional Supplements in Management of Stroke

Abstract: Stroke remains a major cause of human disability worldwide. Interventions and rehabilitation at the poststroke stage are critical for recovery. A single-blinded randomized controlled trial was conducted on 61 patients diagnosed with subacute stage of ischemic stroke. Ingestion of Nattospecs was tested as an adjuvant to support rehabilitation when combined with standard of care (SOC) treatment (electroacupuncture and Naatrapyl) (Trial group) and compared to SOC treatment alone (Control group). After 60 days, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In clinical studies completed to date, the daily dose between studies can vary up to 10 times. Daily doses range from as low as 1,200 FU (25); 2,000 FU (18,(25)(26)(27)(28)(29)(30); 3,000 FU (31); 4,000 FU (17) to higher doses, 6,000 FU (5), 7,000 FU (19) and 13,000 FU (32). We believe that the reason for the wide discrepancies and inconsistencies in the doses is that there have been no authoritative data on the effective dose (ED) or effective concentration (EC) of NK, the minimum effective dose (MED) and the maximum effective dose or the maximum tolerated dose (MTD).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies completed to date, the daily dose between studies can vary up to 10 times. Daily doses range from as low as 1,200 FU (25); 2,000 FU (18,(25)(26)(27)(28)(29)(30); 3,000 FU (31); 4,000 FU (17) to higher doses, 6,000 FU (5), 7,000 FU (19) and 13,000 FU (32). We believe that the reason for the wide discrepancies and inconsistencies in the doses is that there have been no authoritative data on the effective dose (ED) or effective concentration (EC) of NK, the minimum effective dose (MED) and the maximum effective dose or the maximum tolerated dose (MTD).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, a clinic trial on patients diagnosed with subacute stage of ischemic stroke reported that oral administration of four NK capsules (300 FU/capsule) daily for 60 days showed supportive effects on treatment and rehabilitation after ischemic stroke by showing statistically significant improvement of stroke-related symptom [60], encouraging further extensive clinical trials to fully explore the prospect of NK as an alternative to tPA in ischemic stroke. Mechanistically, it is suggested that NK protects brain against ischemia by elevating cAMP level to inhibit platelets, activating JAK1/STAT1 pathway to suppress apoptosis, promoting nitric oxide (NO) level to relax vascular smooth muscle, and increasing fibrinolytic activity to protect endothelial cells.…”
Section: Ischemic Strokementioning
confidence: 97%
“…In these cases, it is essential that the food provided is based on texture-modified foods, with a high caloric density, as well as hyperproteic foods [19]. When this is not possible, supportive feeding by nasogastric tube can be used [20]. Additionally, in these patients we found a microbial profile similar to healthy controls in terms of α-abundance and structure; it was found that patients with LCA presented more producers of short-chain fatty acids, including Odoribacter, Akkermansia, Ruminococcaceae_UCG_005 and Victivallis.…”
Section: The Role Of Sports and Nutrition In Neurological Healthmentioning
confidence: 99%